Reforming the System of Public Procurements in the Context of the European Integration Processes - Sevostjanova Ganna S. (Bìznes Inform, 2015)
The article analyzes reforming the system of public procurements in Ukraine in the context of the European integration processes and provides proposals for further directions of reforming, taking into account successful international practices. As result of research, the system of public procurements and its development in the independent Ukraine, phases of reforming in the context of the European integration processes, as well as compliance of the law of Ukraine of 10.04.2014 No.1197-VII «On fulfillment of public procurements» with standards of the European Union in the field of public procurements were analyzed; the main directions of reforming the public procurement system in accordance with the Association Agreement between Ukraine and the EU has been summarized. It is displayed that, despite a number of shortcomings in the system of public procurements, an active reforming and implementing in the legislation of the main requirements for public procurement in the EU is going on currently. Directions of further reforms of the public procurements system have been suggested. Prospects of the further research will be studying and analyzing international experience in implementing the electronic public procurements with a view to formulating proposals as to the best model for a native procurements system.